Analisis Buku Ajar Matematika: Kesalahan Penyajian Tingkat Kognitif Soal berdasarkan Taksonomi Bloom Revisi - Sriyanti, A.; Mardianti, Mardianti; Nursalam, Nursalam; Munirah, Munirah (Al asma : Journal of Islamic Education, 2025)
Learning materials and exercises in mathematics textbooks play a crucial role, where the materials develop students’ knowledge, while the exercises serve as evaluation tools to measure their understanding. This study aims to identify errors in the presentation of materials based on four mathematical objects and to analyze the cognitive levels of exercises in the topic of Linear Equations from the Grade VIII SMP/MTs mathematics textbook, Curriculum 2013 revision 2017 published by the Ministry of Education and Culture. The research employed a qualitative descriptive method with documentation techniques. The subjects consisted of the materials and exercises from the selected topic, while data analysis was carried out through data reduction, presentation, and conclusion drawing. The findings revealed one factual error and five operational errors, while no conceptual or principle errors were found. The cognitive levels of the exercises were fairly varied, covering LOTS, MOTS, and HOTS. Specifically, there were 3 items at the remembering level (C1/LOTS), 55 at understanding (C2), 23 at applying (C3/MOTS), and 3 at analyzing (C4/HOTS). However, items at the evaluating (C5) and creating (C6) levels were not present. Overall, the exercises were sufficiently varied but unevenly distributed, with a limited number of higher-order thinking items. The implication of this study highlights the need for continuous improvement of mathematics textbooks to ensure more accurate content, a balanced distribution of cognitive levels, and the enhancement of mathematics learning quality as well as overall educational standards in Indonesia.